2014
DOI: 10.1681/asn.2012111101
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MicroRNA-30 Facilitates Podocyte Injury and Is Prevented by Glucocorticoids

Abstract: MicroRNAs (miRNAs) are essential for podocyte homeostasis, and the miR-30 family may be responsible for this action. However, the exact roles and clinical relevance of miR-30s remain unknown. In this study, we examined the expression of the miR-30 family in the podocytes of patients with FSGS and found that all members are downregulated. Treating cultured human podocytes with TGF-b, LPS, or puromycin aminonucleoside (PAN) also downregulated the miR-30 family. Podocyte cytoskeletal damage and apoptosis caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
148
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(159 citation statements)
references
References 43 publications
10
148
1
Order By: Relevance
“…The expressions and functions of miR-196a, miR-30a, and miR-490 miRNAs in their respective tissues also support a role for these miRNAs as potential biomarkers of FSGS disease activity. Previous studies, including ours (22,27), showed that the miR-30 family is strongly expressed in podocytes and that its levels vary with disease state. Dysfunction and/or decrease in miRNAs of the miR-30 family could lead to podocyte apoptosis and depletion, glomerulosclerosis, and proteinuric renal disease.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The expressions and functions of miR-196a, miR-30a, and miR-490 miRNAs in their respective tissues also support a role for these miRNAs as potential biomarkers of FSGS disease activity. Previous studies, including ours (22,27), showed that the miR-30 family is strongly expressed in podocytes and that its levels vary with disease state. Dysfunction and/or decrease in miRNAs of the miR-30 family could lead to podocyte apoptosis and depletion, glomerulosclerosis, and proteinuric renal disease.…”
Section: Discussionmentioning
confidence: 77%
“…We directly screened the distinct expression profile of urinary miRNAs in patients with FSGS-A using a TaqMan Low Density Array, and candidate miRNAs were selected for further analysis. Because previous studies reported that kidneyenriched miRNAs such as the miR-30 (21,22,27) and miR-10 families (28) as well as miRNAs involved in immune responses and inflammation, including miR-155 (29,30) and miR-146a (26,31), have roles in the modulation of renal function, these kidney-specific and immune response-associated miRNAs are also included in the candidate list.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Summarized findings show that miR-34a suppresses brain tumor growth by targeting c-Met and Notch and suggest that miR-34a could serve as a potential therapeutic agent for brain tumors (Li et al, 2009). NOTCH1 is also targeted by down-regulated miR-30 which is demonstrated protecting podocytes by targeting NOTCH1 and TP53 and the loss of it facilitates podocyte injury (Wu et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…Different miRs have been found to be enriched in human kidneys include miR-192, miR-194, miR-204, miR-215 and miR-216 [11]. MiRs are also essential for podocyte homeostasis [12][13][14][15] and can be secreted in body fluids [16,17].…”
mentioning
confidence: 99%